2009
DOI: 10.1002/asi.21185
|View full text |Cite
|
Sign up to set email alerts
|

Assessing global diffusion with Web memetics: The spread and evolution of a popular joke

Abstract: Memes are small units of culture, analogous to genes, which flow from person to person by copying or imitation. More than any previous medium, the Internet has the technical capabilities for global meme diffusion. Yet, to spread globally, memes need to negotiate their way through cultural and linguistic borders. This article introduces a new broad method, Web memetics, comprising extensive Web searches and combined quantitative and qualitative analyses, to identify and assess: (a) the different versions of a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 30 publications
1
33
0
3
Order By: Relevance
“…Meme is a unit of cultural evolution, which realize interpersonal communication through copy or imitation. [1] Compared to traditional media, Internet has more technical capacity to achieve globalized spread of memes. [1] Internet memes is a high-profile phenomenon often referring to a certain kind of behavior, concepts, and popular words that spread quickly on the Internet so as to draw public attention.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Meme is a unit of cultural evolution, which realize interpersonal communication through copy or imitation. [1] Compared to traditional media, Internet has more technical capacity to achieve globalized spread of memes. [1] Internet memes is a high-profile phenomenon often referring to a certain kind of behavior, concepts, and popular words that spread quickly on the Internet so as to draw public attention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[1] Compared to traditional media, Internet has more technical capacity to achieve globalized spread of memes. [1] Internet memes is a high-profile phenomenon often referring to a certain kind of behavior, concepts, and popular words that spread quickly on the Internet so as to draw public attention. [2] It exists in the form of pictures, videos, and spreads among network users through blogs, social networking and so on.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whilst initial hopes for a science of memetics largely evaporated around the middle of the 2000s with the death of the one discipline's one dedicated journal (Edmonds, 2005), interest has been maintained in relation to so 'Internet memes' which includes hared online jokes and other digital material which are subject to forms of evolutionary change (Shifman and Thelwall, 2009, Ward, 2008, Weng et al, 2012, Rintel, 2013, Christensen, 2011, Bauckhage et al, 2013, Shifman, 2012. The term pop-cultural meme was coined as a more accurate distinction with the academic meme as some have suggested that the Internet meme must originate online, rather than simply proliferating there (see discussion in Sparkes- Vian, 2015).…”
Section: Memes Memetics and Propagandamentioning
confidence: 99%
“…In their study of the diffusion of an Internet meme in the form of an online joke, Shifman and Thelwall (2009) noted that the meme they were studying developed a distinctive 'call-response' pattern. In that case, as the initial joke revolved around stereotypical gender roles that pat tern took the form of a male/female call-response.…”
Section: Satire and Critique As Counter-propagandamentioning
confidence: 99%
“…For example, Shifman and Thelwall (2009) tracked the online manifestations of a widely circulated joke and discovered that while the core structure of the joke remained intact, certain elements evolved to become more relevant, and therefore funnier, to different national and cultural groups. Such adoptions and adaptations are consistent with how globalization theorists view the circulation of cultural products through the entanglement of global and local forces (Kraidy, 2005).…”
Section: Participatory Playfulness and Memetic Cynicismmentioning
confidence: 99%